2017
DOI: 10.1002/mp.12354
|View full text |Cite
|
Sign up to set email alerts
|

Real‐time dynamic MR image reconstruction using compressed sensing and principal component analysis (CSPCA): Demonstration in lung tumor tracking

Abstract: A real-time reconstruction technique was developed for adaptive radiotherapy using a Linac-MRI system. Our CS-PCA algorithm can achieve tumor contours with DC greater than 0.9 and NMSE less than 0.06 at acceleration factors of up to, and including, 10×. The reconstruction speed for the Split Bregman CS ranged from 200 to 260 ms, whereas the CS-PCA reconstruction speed ranged from 5 to 20 ms implemented using nonoptimized MATLAB code.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 24 publications
0
23
0
Order By: Relevance
“…), and presence of image artifacts from various sources (including bias field artifacts, which are not corrected for in this study) may all affect image quality and contouring performance. However, in our previous work [30][31][32] we have tested this autocontouring algorithm with images degraded retrospectively by additional noise and k-space undersampling, and has shown that the algorithm works reasonably well with lower image quality scenarios, albeit with slightly poorer performance metrics.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…), and presence of image artifacts from various sources (including bias field artifacts, which are not corrected for in this study) may all affect image quality and contouring performance. However, in our previous work [30][31][32] we have tested this autocontouring algorithm with images degraded retrospectively by additional noise and k-space undersampling, and has shown that the algorithm works reasonably well with lower image quality scenarios, albeit with slightly poorer performance metrics.…”
Section: Discussionmentioning
confidence: 99%
“…To present the results, the following notation is used: A 12 represents autocontours trained by expert 1 in session 2; whereas M 31 denotes manual contours drawn by expert 3 in session 1. The automatic contouring algorithm, trained using the contours from 30 training images (images 1-30) from each of the 6 manual contouring sessions (3 contourer 9 2 sessions) is used to generate 6 sets of 100 automatic contours (ROI AUTO ) on the 100 tracking images (images 31-130), labeled as A 11 , A 12 , A 21 , A 22 , A 31 , A 32 . These are compared against the 6 sets of manual contours (ROI STD ) drawn on the same tracking images, namely, M 11 , M 12 , M 21 , M 22 , M 31 , M 32.…”
Section: D Evaluation Of Contoursmentioning
confidence: 99%
See 2 more Smart Citations
“…Of all available imaging modalities for IGRT, MRI is the most versatile and suitable candidate as it provides soft-tissue contrast to enable direct tumour visualization as well as OAR localization (Lagendijk et al 2014). Moreover, it provides real-time imaging to characterize and eventually track anatomical motion (Stemkens et al 2016, Dietz et al 2017 for MRI guided radiotherapy and for dose reconstruction (Glitzner et al 2015) and ultimately real-time plan adaptation (Kontaxis et al 2017).…”
Section: Introductionmentioning
confidence: 99%